Reconciling structure prediction of alloyed, ultrathin nanowires with spectroscopy. Issue 20 (26th April 2021) - McGuire, Scott C.; Ebrahim, Amani M.; Hurley, Nathaniel; Zhang, Lihua; Frenkel, Anatoly I.; Wong, Stanislaus S.
Abstract : EDS and EXAFS spectroscopy are used as complementary techniques to investigate the local structure of bimetallic ultrathin nanowires. Results highlight the importance of using a combined approach to achieve an accurate understanding of these systems. Abstract : A number of complementary, synergistic advances are reported herein. First, we describe the 'first-time' synthesis of ultrathin Ru2 Co1 nanowires (NWs) possessing average diameters of 2.3 ± 0.5 nm using a modified surfactant-mediated protocol. Second, we utilize a combination of quantitative EDS, EDS mapping (along with accompanying line-scan profiles), and EXAFS spectroscopy results to probe the local atomic structure of not only novel Ru2 Co1 NWs but also 'control' samples of analogous ultrathin Ru1 Pt1, Au1 Ag1, Pd1 Pt1, and Pd1 Pt9 NWs. We demonstrate that ultrathin NWs possess an atomic-level geometry that is fundamentally dependent upon their intrinsic chemical composition. In the case of the PdPt NW series, EDS mapping data are consistent with the formation of a homogeneous alloy, a finding further corroborated by EXAFS analysis. By contrast, EXAFS analysis results for both Ru1 Pt1 and Ru2 Co1 imply the generation of homophilic structures in which there is a strong tendency for the clustering of 'like' atoms; associated EDS results for Ru1 Pt1 convey the same conclusion, namely the production of a heterogeneous structure. Conversely, EDS mapping data for Ru2 Co1 suggests a uniform distribution of both elements. In the singular case of Au1 Ag1, EDS mapping results are suggestive of a homogeneous alloy, whereas EXAFS analysis pointed to Ag segregation at the surface and an Au-rich core, within the context of a core–shell structure. These cumulative outcomes indicate that only a combined consideration of both EDS and EXAFS results can provide for an accurate representation of the local atomic structure of ultrathin NW motifs.